2010
DOI: 10.1246/cl.2010.586
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state Solvatochromic Behavior of Reichardt’s Dye Crystals Hybridized with Silica Nanoparticles

Abstract: The dry bead milling of solvatochromic ET30 with silica nanoparticles gave powdery nanohybrids, which exhibited color changes depending on environmental conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…It was reported that dye 1 adsorbed to silica exhibits an orange-red color [λ max = 497 nm; E T (30) = 57.5 kcal mol –1 ], while a red-violet color occurs when the dye is adsorbed onto non-dried cellulose [λ max = 539 nm; E T (30) = 53.0 kcal mol –1 ] . The same dye exhibits a green color when it is adsorbed to macroporous polystyrene [λ max = 752 nm; E T (30) = 38.0 kcal mol –1 ]. , Ichimura et al used dry-bead milling of betaine dye 1 with surface-modified silica nanopowder to produce nanohybrid particles, the color of which depends notably on the external atmosphere and is green (λ max of the diffusion reflection spectra = 695 nm), blue (619 nm), and purple (566 nm) under dry, ambient, and wet conditions (Δλ = −129 nm; Δν̅ max = +3279 cm –1 ), according to the increase in surface polarity. Table shows the E T (30) and normalized E T N values determined for various inorganic and organic solid materials.…”
Section: Pyridinium N-phenolate Dyes As Probes To Measure the Polarit...mentioning
confidence: 99%
“…It was reported that dye 1 adsorbed to silica exhibits an orange-red color [λ max = 497 nm; E T (30) = 57.5 kcal mol –1 ], while a red-violet color occurs when the dye is adsorbed onto non-dried cellulose [λ max = 539 nm; E T (30) = 53.0 kcal mol –1 ] . The same dye exhibits a green color when it is adsorbed to macroporous polystyrene [λ max = 752 nm; E T (30) = 38.0 kcal mol –1 ]. , Ichimura et al used dry-bead milling of betaine dye 1 with surface-modified silica nanopowder to produce nanohybrid particles, the color of which depends notably on the external atmosphere and is green (λ max of the diffusion reflection spectra = 695 nm), blue (619 nm), and purple (566 nm) under dry, ambient, and wet conditions (Δλ = −129 nm; Δν̅ max = +3279 cm –1 ), according to the increase in surface polarity. Table shows the E T (30) and normalized E T N values determined for various inorganic and organic solid materials.…”
Section: Pyridinium N-phenolate Dyes As Probes To Measure the Polarit...mentioning
confidence: 99%
“…We have recently observed that solvatochromic Reichardt's dye E T 30 in the solid state suffers considerably from blue shift in diffusive reflection spectra when the dye is nanohybridised with m-SiO 2 to give nanopowders and exposed to water, implying the specific contact of surface molecules with water. 18 In analogy to this sort of surfacespecific behaviour of organic crystals, a portion of DPA molecules at the topmost surfaces of crystals is released from the confinement of crystal lattice to display monomeric absorption spectra.…”
Section: Fluorescence Behaviour Of Hybridsmentioning
confidence: 99%
“…15 Historically, these color-changing dyes have been studied in liquid phase and characterized using UV-Vis absorption spectroscopy; however, some recent work has used individual solvatochromic dyes in solids (e.g., films of dyes entrapped in porous, semi-liquid, or polymer matrices). [21][22][23][24][25] Prior colorimetric sensor arrays produced from our lab have included only one or two solvatochromic sensor spots, but the response of an array of solvatochromic dyes in the solid-state has not been previously examined.We report here a colorimetric sensor array that utilizes solvatochromic dyes in semi-liquid matrices to differentiate eleven common organic solvents. Importantly, the solvatochromic dyes serve a dual function: (1) to change color with a change in local polarity and (2) to facilitate the measurement of physical changes in their matrix caused by solvent sorption.…”
mentioning
confidence: 99%
“…15 Historically, these color-changing dyes have been studied in liquid phase and characterized using UV-Vis absorption spectroscopy; however, some recent work has used individual solvatochromic dyes in solids (e.g., films of dyes entrapped in porous, semi-liquid, or polymer matrices). [21][22][23][24][25] Prior colorimetric sensor arrays produced from our lab have included only one or two solvatochromic sensor spots, but the response of an array of solvatochromic dyes in the solid-state has not been previously examined.…”
mentioning
confidence: 99%